Malnutrition and Its Influence on Gut sIgA–Microbiota Dynamics - Monica Profir; Robert Mihai Enache; Oana Alexandra Roşu; Luciana Alexandra Pavelescu; Sanda Maria Creţoiu; Bogdan Severus Gaspar (Biomedicines)
In the current era, malnutrition is seen as both undernutrition and overweight and obesity; both conditions are caused by nutrient deficiency or excess and improper use or imbalance in the intake of macro and micronutrients. Recent evidence suggests that malnutrition alters the intestinal microbiota, known as dysbiosis. Secretory immunoglobulin A (sIgA) plays an important role in maintaining and increasing beneficial intestinal microbiota populations and protecting against pathogenic species. Depletion of beneficial bacterial populations throughout life is also conditioned by malnutrition. This review aims to synthesize the evidence that establishes an interrelationship between diet, malnutrition, changes in the intestinal flora, and sIgA levels. Targeted nutritional therapies combined with prebiotic, probiotic, and postbiotic administration can restore the immune response in the intestine and the host’s homeostasis.